Porous all-solid-waste-based geopolymer and preparation method thereof

By optimizing the ratio of slag and fly ash and using alkaline exciters to form C-A-S-H and N-A-S-H composite gels, the problems of geological polymer materials in pore structure regulation are solved, pore distribution uniformity and volume stability are achieved, and thermal insulation and mechanical properties are taken into account, which is suitable for high-performance building materials.

CN119822665APending Publication Date: 2025-04-15HEILONGJIANG INST OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510134392.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When regulating the pore structure, existing geological polymer materials tend to lead to uneven pore size distribution, difficult to achieve structural controllability, and negatively affect environmental friendliness. At the same time, the consistency of material strength and performance is poor, which limits its further promotion in the field of high-performance building materials.

Method used

By optimizing the ratio of slag to fly ash to 1:3 and combining with the use of alkaline exciters, C-A-S-H and N-A-S-H composite gels are formed to optimize the reaction product structure and achieve pore distribution uniformity and volume stability.

Benefits of technology

It achieves pore distribution uniformity and volume stability, takes into account the balance of thermal insulation and mechanical properties, improves the thermal insulation and strength characteristics of the material, and is suitable for various high-performance demand scenarios such as building heat insulation and fire protection, while reducing production costs and improving the green and environmentally friendly performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822665A_ABST
    Figure CN119822665A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly discloses a porous all-solid-waste-based geopolymer and a preparation method thereof, the porous all-solid-waste-based geopolymer is composed of 25 parts by weight of slag, 75 parts by weight of fly ash, 27.08-54.33 parts by weight of an alkali activator and 12.48-26.24 parts by weight of water; the modulus of the alkaline activator is 0.8-1.4, and the alkaline activator is composed of sodium silicate water glass and sodium hydroxide. Compared with the prior art, the geopolymer has the advantages that the ratio of the slag to the fly ash is optimized to be 1: 3, and the alkaline activator is used, so that the prepared geopolymer has high porosity, uniform pore size distribution and excellent heat insulation performance, and meanwhile, good mechanical strength is kept under the condition of high porosity; industrial solid waste is used as a main raw material, a foaming agent or aluminum powder is not needed, the environmental pollution and the preparation cost are reduced, and the preparation process is simple and convenient and suitable for large-scale industrial application; the developed material not only meets the environmental protection requirements of green building materials, but also has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a porous all-solid waste-based geopolymer and a preparation method thereof. Background Art

[0002] As a green building material, geopolymer has been widely used in the construction field in recent years. It uses industrial waste (such as fly ash, slag, kaolin, etc.) as the main raw material and is solidified through alkali activation technology. It has significant advantages such as high temperature resistance, chemical corrosion resistance, and low carbon emissions.

[0003] Chinese patent application number CN201610126820.4 discloses a fly ash geopolymer porous material and a manufacturing process thereof, wherein the component proportions by weight are: 60-100 parts of fly ash, 40-70 parts of alkali activator, 0-40 parts of admixture, 0-5 parts of glass fiber, 2-8 parts of physical foaming agent, and 0-0.8 parts of chemical activator. The alkali activator is an alkaline mixed solution containing multiple ions, composed of industrial water glass, sodium hydroxide, water, polyethylene glycol, and sodium phosphate. The admixture refers to ground metakaolin, microsilica powder, and calcined coal gangue. The physical foaming agent includes expired shampoo, anionic surfactant sodium dodecyl sulfate (SDS), fatty alcohol polyoxyethylene ether sodium sulfate (AES), and fatty alcohol polyoxyethylene ether sulfosuccinic acid monoester disodium salt (AESS). The chemical foaming agent includes aluminum powder, hydrogen peroxide, etc. The present invention has the advantages of adjustable volume density, small and uniform pore size, low thermal conductivity, high strength, the same lifespan as the building, and good fireproof performance.

[0004] Chinese patent application number CN202111153021.3 discloses a preparation method and application of a porous geopolymer material. The geopolymer adsorption material uses casting dust as raw material, water glass and sodium hydroxide as stimulants, oleic acid and hydrogen peroxide as foaming agents and foam stabilizers, and finally obtains the porous geopolymer adsorption material by a mold shaping method; the porous geopolymer material of the present invention converts casting dust into high value-added products, realizes the resource utilization of casting dust, and provides a new way for the foundry industry to treat casting dust. The porous geopolymer material prepared by the present invention has high added value for Pb 2+ The maximum adsorption capacity can reach 251.56 mg / g for Ni 2+ The maximum adsorption capacity can reach 60.16 mg / g, which has excellent heavy metal adsorption effect and is conducive to the promotion of casting dust recycling.

[0005] The pore structure control technologies of the above-mentioned geopolymers mostly use foaming agents (such as hydrogen peroxide) or aluminum powder for chemical pore formation. These methods can generate porous materials to a certain extent, but they also have many shortcomings. For example, the foaming agent may lead to uneven pore size distribution, making it difficult to achieve controllable structure; although aluminum powder foaming can increase porosity, it is easy to introduce bubble segregation and have a negative impact on environmental friendliness. In addition, these methods are often accompanied by a decrease in material strength when regulating the pore structure, and the stability of the preparation process and the consistency of performance are poor, which limits their further promotion in the field of high-performance building materials. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a porous all-solid waste-based geopolymer and a preparation method thereof.

[0007] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0008] One of the technical solutions of the present invention is a porous all-solid waste-based geopolymer, which is composed of 25 parts by weight of slag, 75 parts by weight of fly ash, 27.08-54.33 parts by weight of alkaline activator and 12.48-26.24 parts by weight of water; the alkaline activator has a modulus of 0.8-1.4 and is composed of sodium silicate water glass and sodium hydroxide.

[0009] Furthermore, the slag is composed of the following chemical components in weight percentage: 32.83% SiO2, 17.19% Al2O3, 36.69% CaO, 0.38% Fe2O3, 8.20% MgO and 1.94% SO3; the fly ash is composed of the following chemical components in weight percentage: 47.98% SiO2, 17.09% Al2O3, 8.00% CaO, 5.16% Fe2O3, 0.68% MgO and 0.23% SO3.

[0010] Preferably, the alkaline activator has a modulus of 1.2.

[0011] Furthermore, in the alkaline activator, the sodium silicate water glass is 22.08-44.33 parts by weight, and the sodium hydroxide is 5-10 parts by weight.

[0012] The second technical solution of the present invention is a method for preparing a porous all-solid waste-based geopolymer, comprising the following steps:

[0013] S1. Raw material preparation: weigh slag and fly ash according to the ratio, mix to form a precursor; dissolve sodium hydroxide in water, stir until completely dissolved, add sodium silicate water glass to form a uniform solution, i.e., alkaline activator, and let the alkaline activator cool to room temperature;

[0014] S2, dry mixing and wet mixing: Place the precursor in a mixer and dry mix for 2 minutes, then add the alkaline activator, stir at a low speed for 1 minute, stop the mixer to clean the slurry hanging on the wall of the mixing pot, and stir quickly for 1 minute to form a uniform slurry;

[0015] S3, molding and vibrating: pour the slurry into the mold, vibrate to remove bubbles, cover with film and let it stand;

[0016] S4. Curing: Leave to stand for 24 hours under standard curing conditions of 20°C and relative humidity RH>95% and then remove from the mould. Then continue to cure in a standard curing box to the specified age.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1) The present invention optimizes the ratio of slag to fly ash to 1:3 and then uses an alkaline activator. The introduction of fly ash can optimize the reaction product structure of slag to form CASH and NASH composite gels. However, in the early stage, due to the slow dissolution rate and low activity of fly ash, less reaction products are generated, and it is difficult to quickly form a large number of reaction products in the early stage, which will cause the pore structure to be unable to be fully filled in the early stage, thereby increasing the porosity, but partially reducing the early strength of the material; the geopolymer prepared by the present invention exhibits excellent pore distribution uniformity and volume stability under high porosity conditions, solves the problems of bubble segregation and uneven pore size distribution in traditional foaming technology, and takes into account the balance requirements of thermal insulation and mechanical properties; effectively improves the microstructure of the material, so that it has higher thermal insulation and good strength characteristics, and is suitable for a variety of high-performance demand scenarios such as building insulation and fire protection.

[0019] 2) In terms of environmental protection and economy, the present invention makes full use of industrial solid waste (slag and fly ash) as the main raw materials, reduces dependence on natural resources, reduces the amount of stimulant used, avoids the use of traditional foaming agents or aluminum powder, thereby significantly reducing production costs and improving the green environmental performance of the material. The preparation process of the present invention is simple and efficient, and through standardized stirring and curing processes, the consistency of material properties and the operability of the preparation process are ensured. Compared with traditional technologies, the present invention not only avoids complex foaming and post-processing steps, but also provides a stable and reliable preparation method suitable for large-scale industrial production.

[0020] 3) The geopolymer material of the present invention has the characteristics of high temperature resistance, chemical corrosion resistance, low carbon and environmental protection, and provides an innovative solution for the fields of low-carbon construction, green building materials and resource utilization. Through system optimization from raw materials to processes, the present invention successfully overcomes the problems of insufficient pore structure regulation, unstable performance and lack of environmental friendliness in the prior art, and has significant promotion and application value and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a microscopic morphology of the slag-fly ash geopolymer 1d obtained in Example 1 of the present invention.

[0022] Figure 2 This is a microscopic morphology of the slag-fly ash geopolymer 3d obtained in Example 1 of the present invention.

[0023] Figure 3 This is a microscopic morphology of the slag-fly ash geopolymer 1d obtained in Example 2 of the present invention.

[0024] Figure 4 This is a microscopic morphology of the slag-fly ash geopolymer 3d obtained in Example 2 of the present invention.

[0025] Figure 5 This is a microscopic morphology of the slag-fly ash geopolymer 1d obtained in Comparative Example 1 of the present invention.

[0026] Figure 6 This is a microscopic morphology of the slag-fly ash geopolymer 3d obtained in Comparative Example 1 of the present invention.

[0027] Figure 7 This is a microscopic morphology of the slag-fly ash geopolymer 1d obtained in Comparative Example 2 of the present invention.

[0028] Figure 8 This is a microscopic morphology of the slag-fly ash geopolymer 3d obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0030] The raw materials and reagents used in the following examples are all commercially available unless otherwise specified. Among them, the slag is composed of the following chemical components in weight percentage: 32.83% SiO2, 17.19% Al2O3, 36.69% CaO, 0.38% Fe2O3, 8.20% MgO and 1.94% SO3; the fly ash is composed of the following chemical components in weight percentage: 47.98% SiO2, 17.09% Al2O3, 8.00% CaO, 5.16% Fe2O3, 0.68% MgO and 0.23% SO3; the water glass modulus of the commercially available sodium silicate water glass is between 2.4 and 3.2.

[0031] Example 1

[0032] This example exemplifies a porous all-solid waste-based geopolymer, which is composed of 25g slag, 75g fly ash, 22.08g sodium silicate water glass, 5g sodium hydroxide and 26.24g water; the specific preparation process is as follows:

[0033] 1) Raw material preparation: weigh slag and fly ash according to the ratio, mix to form a precursor; at the same time, dissolve sodium hydroxide in water, stir until completely dissolved, add sodium silicate water glass to form a uniform solution, i.e., an alkaline activator with a modulus of 1.2, and let the alkaline activator cool to room temperature;

[0034] 2) Dry mixing and wet mixing: Place the precursor in a mixer and dry mix for 2 minutes, then add the alkaline activator, stir at a low speed for 1 minute, stop the mixer to clean the slurry hanging on the wall of the mixing pot, and stir quickly for 1 minute to form a uniform slurry;

[0035] 3) Molding and vibrating: Pour the slurry into the mold, vibrate to remove bubbles, cover with film and let it stand;

[0036] 4) Curing: The sample was placed under standard curing conditions of 20° C. and relative humidity RH>95% for 24 hours and then demoulded. The sample was then cured in a standard curing box for 28 days to obtain Sample 1.

[0037] Example 2

[0038] The difference from Example 1 is that the porous all-solid waste-based geopolymer exemplarily demonstrated in this example is composed of 25 g of slag, 75 g of fly ash, 33.24 g of sodium silicate water glass, 7.5 g of sodium hydroxide and 19.37 g of water, and finally sample 2 is prepared.

[0039] Comparative Example 1

[0040] The difference from Example 1 is that the porous all-solid waste-based geopolymer exemplarily demonstrated in this example is composed of 75 g of slag, 25 g of fly ash, 22.08 g of sodium silicate water glass, 5 g of sodium hydroxide and 26.24 g of water, and finally sample 3 is prepared.

[0041] Comparative Example 2

[0042] The difference from Example 1 is that the porous all-solid waste-based geopolymer exemplarily demonstrated in this example is composed of 50 g of slag, 50 g of fly ash, 44.33 g of sodium silicate water glass, 10 g of sodium hydroxide and 12.48 g of water, and finally sample 4 is prepared.

[0043] The flexural strength and compressive strength of samples 1 to 4 were tested according to GB / T 17671-2021 standard, and the pore structure of the samples was characterized using a Micromeritics AutoPore IV 9500 mercury intrusion instrument:

[0044] The 28d flexural strength of sample 1 is 4.4MPa, the 28d compressive strength is 36.2MPa, the 1d porosity is 42.53%, the 3d porosity is 37.48%, the 28d porosity is 23.89%, and the 1d bulk density is 1.45g / cm 3 , 3d bulk density is 1.46 g / cm 3 , 28d bulk density is 1.47g / cm 3 ; 1d and 3d SEM images of sample 1 are as follows Figure 1 and Figure 2 As shown by Figure 1 and Figure 2 It can be seen that the slag-fly ash-based geopolymer of sample 1 becomes gradually denser with the increase of age.

[0045] The 28d flexural strength of sample 2 is 4.6MPa, the 28d compressive strength is 42.3MPa, the 1d porosity is 37.58%, the 3d porosity is 22.50%, the 28d porosity is 21.78%, and the 1d bulk density is 1.54g / cm 3 , 3d bulk density is 1.53 g / cm 3 , 28d bulk density is 1.49g / cm 3 , the 1d and 3d SEM images of sample 2 are as follows Figure 3 and Figure 4 As shown by Figure 3 and Figure 4 It can be seen that the slag-fly ash-based geopolymer of sample 2 becomes gradually denser with the increase of age.

[0046] Depend on Figure 1-Figure 4 It can be seen that the early strength of Sample 1 and Sample 2 is reduced, but still meets the construction requirements; and Sample 1 and Sample 2 show excellent pore distribution uniformity and volume stability under high porosity conditions, while taking into account the balance requirements of mechanical properties.

[0047] The 28d flexural strength of sample 3 is 4.8MPa, the 28d compressive strength is 62.3MPa, the 1d porosity is 13.61%, the 3d porosity is 10.08%, the 28d porosity is 5.30%, and the 1d bulk density is 1.60g / cm 3 , 3d bulk density is 1.62g / cm 3 , 28d bulk density is 1.63g / cm 3 , the 1d and 3d SEM images of sample 3 are as follows Figure 5 and Figure 6 As shown by Figure 5 and Figure 6It can be seen that when the ratio of slag to fly ash is 3:1, the porosity of sample 3 is lower than that of sample 1 and sample 2, and the slag-fly ash-based geopolymer of sample 3 gradually becomes denser with the increase of age.

[0048] The 28d flexural strength of sample 4 is 6.8 MPa, the 28d compressive strength is 64.8 MPa, the 1d porosity is 14.23%, the 3d porosity is 8.45%, the 28d porosity is 6.60%, and the 1d bulk density is 1.68 g / cm 3 , 3d bulk density is 1.67 g / cm 3 , 28d bulk density is 1.65g / cm 3 , the 1d and 3d SEM images of sample 4 are as follows Figure 7 and Figure 8 As shown by Figure 7 and Figure 8 It can be seen that when the ratio of slag to fly ash is 1:1, the porosity of sample 4 is lower than that of sample 1 and sample 2, but it is still higher than the porosity of sample 3; the slag-fly ash-based geopolymer of sample 4 gradually becomes denser with the increase of age.

[0049] In summary, the present invention optimizes the ratio of slag to fly ash to 1:3 and then uses an alkaline activator. The introduction of fly ash can optimize the reaction product structure of slag to form CASH and NASH composite gels. However, in the early stage, due to the slow dissolution rate and low activity of fly ash, less reaction products are generated, and it is difficult to quickly form a large number of reaction products in the early stage, which will cause the pore structure to be unable to be fully filled in the early stage, thereby increasing the porosity, but partially reducing the early strength of the material; the geopolymer prepared by the present invention exhibits excellent pore distribution uniformity and volume stability under high porosity conditions.

[0050] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A porous all-solid waste-based geopolymer, characterized in that: The invention comprises 25 parts by weight of slag, 75 parts by weight of fly ash, 27.08-54.33 parts by weight of alkaline activator and 12.48-26.24 parts by weight of water; the alkaline activator has a modulus of 0.8-1.4 and is composed of sodium silicate water glass and sodium hydroxide.

2. The porous all-solid waste-based geopolymer according to claim 1, characterized in that: The slag is composed of the following chemical components in weight percentage: 32.83% SiO2, 17.19% Al2O3, 36.69% CaO, 0.38% Fe2O3, 8.20% MgO and 1.94% SO3; the fly ash is composed of the following chemical components in weight percentage: 47.98% SiO2, 17.09% Al2O3, 8.00% CaO, 5.16% Fe2O3, 0.68% MgO and 0.23% SO3.

3. The porous all-solid waste-based geopolymer according to claim 1, characterized in that: The alkaline activator has a modulus of 1.

2.

4. The porous all-solid waste-based geopolymer according to claim 1, characterized in that: The alkaline activator contains 22.08-44.33 parts by weight of sodium silicate water glass and 5-10 parts by weight of sodium hydroxide.

5. A method for preparing a porous all-solid waste-based geopolymer according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Raw material preparation: weigh slag and fly ash according to the ratio, mix to form a precursor; dissolve sodium hydroxide in water, stir until completely dissolved, add sodium silicate water glass to form a uniform solution, i.e., alkaline activator, and let the alkaline activator cool to room temperature; S2, dry mixing and wet mixing: Place the precursor in a mixer and dry mix for 2 minutes, then add the alkaline activator, stir at a low speed for 1 minute, stop the mixer to clean the slurry hanging on the wall of the mixing pot, and stir quickly for 1 minute to form a uniform slurry; S3, molding and vibrating: pour the slurry into the mold, vibrate to remove bubbles, cover with film and let it stand; S4. Curing: Leave to stand for 24 hours under standard curing conditions of 20°C and relative humidity RH>95% and then remove from the mould. Then continue to cure in a standard curing box to the specified age.

Citation Information

Patent Citations

  • Flyash geopolymer based porous material and preparation process thereof

    CN105800972A

  • Preparation method and application of porous geopolymer material

    CN113831068A